Design a Smart Solar Tracker to Increase Energy Output Power Generated in Solar Home System - Eka Saputra, Yuli Mafendro Dedet; Ramadhan, Mochammad Tendi Noer; Maulida, Azzahra; Santoso, Budi; Basri, Ismail (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
This research proposes the use of a smart solar tracker to enhance the power generated by solar panels. The smart solar tracker is designed by integrating IoT technology and applied to a Solar Home System. This device not only optimizes the tilt angle of solar panels automatically but also enables remote monitoring of solar panel performance through IoT. Parameters such as panel angle, voltage, and current are measured. Test results indicate that installing the smart solar tracker increases the power output of solar panels compared to panels without the smart solar tracker. For instance, at 11:00 AM, solar panels with the smart solar tracker generated 9.85W of power with a panel angle of 70 degrees, whereas solar panels without the smart solar tracker only produced 8.9W of power with a panel angle of 35 degrees. Penelitian ini mengusulkan penggunaan smart solar tracker untuk meningkatkan daya yang dihasilkan oleh panel surya. Smart solar tracker dirancang dengan mengintegrasikan teknologi IoT dan diterapkan pada Solar Home System. Alat ini tidak hanya mengoptimalkan sudut kemiringan panel surya secara otomatis, tetapi juga memungkinkan pemantauan jarak jauh terhadap kinerja panel surya melalui IoT. Pengukuran parameter seperti sudut panel, tegangan, dan arus dilakukan. Hasil pengujian menunjukkan bahwa pemasangan smart solar tracker meningkatkan daya output panel surya dibandingkan dengan panel surya tanpa smart solar tracker. Misalnya, pada pukul 11.00 WIB, panel surya dengan smart solar tracker menghasilkan daya sebesar 9.85W dengan sudut panel 70 derajat, sementara panel surya tanpa smart solar tracker hanya menghasilkan daya sebesar 8.9W dengan sudut panel 35 derajat.